2016
DOI: 10.1136/annrheumdis-2015-208441
|View full text |Cite
|
Sign up to set email alerts
|

Decreased SMG7 expression associates with lupus-risk variants and elevated antinuclear antibody production

Abstract: Objectives Following up the SLE GWAS identification of NMNAT2 at rs2022013, we fine-mapped its 150kb flanking regions containing NMNAT2 and SMG7 in a 15,292 case-control multi-ancestry population and tested functions of identified variants. Methods We performed genotyping using custom array, imputation by IMPUTE 2.1.2, and allele specific functions using qRT-PCR and luciferase reporter transfections. SLE PBMCs were cultured with siRNAs to measure antinuclear antibody (ANA) and cyto/chemokine levels in supern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Our gene-level analysis showed that rs66977652 confers a significant eQTL effect on SMG7 (P=3.1×10 -15 in whole blood; Fig. 4c and Supplementary Figure 3) , suggesting the secondary signal might influence the risk of SLE by modulating SMG7 expression, which is supported by functional studies 39 . These findings suggest two potential effector genes, NCF2 and SMG7 , in a single locus 25,26 .…”
Section: Main Textsupporting
confidence: 73%
“…Our gene-level analysis showed that rs66977652 confers a significant eQTL effect on SMG7 (P=3.1×10 -15 in whole blood; Fig. 4c and Supplementary Figure 3) , suggesting the secondary signal might influence the risk of SLE by modulating SMG7 expression, which is supported by functional studies 39 . These findings suggest two potential effector genes, NCF2 and SMG7 , in a single locus 25,26 .…”
Section: Main Textsupporting
confidence: 73%
“…95] shows all the risk loci for SLE and pSS that have been clearly replicated and confirmed up to date.…”
mentioning
confidence: 79%
“…The mechanism appears to involve promotion of ATM-dependent phosphorylation and subsequent inhibition of the E3 ubiquitin ligase mouse double minute 2 homolog (MDM2). This role for SMG7 may well have an impact on expression/function of p53 and recovery from AKI, particularly in patients with lupus nephitis who exhibit reduced expression of SMG7 [111]. The participation of MDM2 in fibrosis, however, is complex.…”
Section: Mechanism Of P53 Activation By Tgf-β1mentioning
confidence: 99%